Differences in Enzymatic Properties of the Saccharomyces kudriavzevii and Saccharomyces uvarum Alcohol Acetyltransferases and Their Impact on Aroma-Active Compounds Production - Stribny, Jiri; Querol, Amparo; Pérez-Torrado, Roberto (Frontiers in Microbiology, 2016)
Abstract Higher alcohols and acetate esters belong to the most important yeast secondary metabolites that significantly contribute to the overall flavour and aroma profile of fermented products. In Saccharomyces cerevisiae, esterification of higher alcohols is catalysed mainly by the alcohol acetyltransferases encoded by genes ATF1 and ATF2. Previous investigation has shown other Saccharomyces species, e.g. S. kudriavzevii and S. uvarum, to vary in aroma-active higher alcohols and acetate esters formation when compared to S. cerevisiae. Here, we aimed to analyse the enzymes encoded by the ATF1 and ATF2 genes from S. kudriavzevii (SkATF1, SkATF2) and S. uvarum (SuATF1, SuATF2). The heterologous expression of the individual ATF1 and ATF2 genes in a host S. cerevisiae resulted in the enhanced production of several higher alcohols and acetate esters. Particularly, an increase of 2-phenylethyl acetate production by the strains that harboured ATF1 and ATF2 genes from S. kudriavzevii and S. uvarum was observed. When grown with individual amino acids as the nitrogen source, the strain that harboured SkATF1 showed particularly high 2-phenylethyl acetate production and the strains with introduced SkATF2 or SuATF2 revealed increased production of isobutyl acetate, isoamyl acetate, and 2-phenylethyl acetate compared to the reference strains with endogenous ATF genes. The alcohol acetyltransferase activities of the individual Atf1 and Atf2 enzymes measured in the cell extracts of the S. cerevisiae atf1 atf2 iah1 triple-null strain were detected for all the measured substrates. This indicated that S. kudriavzevii and S. uvarum Atf enzymes had broad range substrate specificity as S. cerevisiae Atf enzymes. Individual Atf1 enzymes exhibited markedly different kinetic properties since SkAtf1p showed c. 2-fold higher and SuAtf1p c. 3-fold higher Km for isoamyl alcohol than ScAtf1p. Together these results indicated that the differences found among the three Saccharomyces species during the aroma-active acetate ester formation may be due, to some extent, to the distinct properties of Atf enzymes.